2018
DOI: 10.1021/acssuschemeng.8b04262
|View full text |Cite
|
Sign up to set email alerts
|

Unlock the Compact Structure of Lignocellulosic Biomass by Mild Ball Milling for Ethylene Glycol Production

Abstract: Ball milling pretreatment was found to be an efficient method to promote the catalytic conversion of lignocellulosic biomass to ethylene glycol (EG). After 3–6 h ball milling of Miscanthus at 450 rpm, the EG yield reached about 52%, which is comparable to the result of pure cellulose conversion. The reasons of the promotion effect were investigated by characterizing the structure of biomass and the reaction residuals with X-ray diffraction, scanning electron microscopy, particle size distribution analyzer, con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(26 citation statements)
references
References 73 publications
1
24
0
1
Order By: Relevance
“…Particle size was identified as a key parameter affecting cellulose hydrolysis potential (Barakat et al, 2014;Vaidya et al, 2016). The reduction of particle size through milling, grinding, and extrusion could enhance the affinity between cellulose and enzymes, deconstruct lignocellulose compact structure and thus increase the rate of hydrolysis (Silva et al, 2012;Pang et al, 2018;Yu et al, 2019). Studies have demonstrated that mechanical deconstruction facilitates enzymatic hydrolysis of various feedstocks such as wood chips (Jiang et al, 2017), miscanthus and wheat straw (Kim et al, 2018) and corn stover (Yu et al, 2019).…”
Section: Particle Sizementioning
confidence: 99%
“…Particle size was identified as a key parameter affecting cellulose hydrolysis potential (Barakat et al, 2014;Vaidya et al, 2016). The reduction of particle size through milling, grinding, and extrusion could enhance the affinity between cellulose and enzymes, deconstruct lignocellulose compact structure and thus increase the rate of hydrolysis (Silva et al, 2012;Pang et al, 2018;Yu et al, 2019). Studies have demonstrated that mechanical deconstruction facilitates enzymatic hydrolysis of various feedstocks such as wood chips (Jiang et al, 2017), miscanthus and wheat straw (Kim et al, 2018) and corn stover (Yu et al, 2019).…”
Section: Particle Sizementioning
confidence: 99%
“…The morphology, particle size, and surface properties of biomass play a crucial role in its conversion [ 24 ], therefore such characteristics were investigated first. The SEM images in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Despite some unresolved issues, many reported catalysts possess excellent catalytic properties and stability in hydrothermal conditions, which allowed their successful testing not only in the conversion of pure microcrystalline cellulose, but also for cellulose containing materials such as cotton, cotton wool, paper (Ribeiro et al, 2017a,d, 2018b), wood lignocellulosic biomass (Yamaguchi et al, 2016; Ribeiro et al, 2018b; Xiao et al, 2018b; Pang et al, 2019), corn stalks, millet, sugarcane, etc. (Liu et al, 2017; Li et al, 2018a), which demonstrates a promising outlook for the future development of multi tonnage production of value-added chemicals and fuels from cellulose biomass.…”
Section: Discussionmentioning
confidence: 99%